Iskolán kívüli színterek az általános iskolai oktatásban - Fűz, Nóra (Magyar Pedagógia, 2017)
In recent decades, out-of-school learning has received increasing attention among teachers, researchers and education experts throughout the world. Out-of-school learning places are characterised by a more life-like and experience-rich environment than the classroom, allowing them to render abstract science knowledge more accessible to students and thus to aid them in achieving a deeper understanding of the material and to apply that knowledge to everyday life. Several international research projects have shown that these programmes exert a positive effect on students’ interest in science and learning motivation while also supporting a choice of career in science. In Hungary, however, we know little about the prevalence, quality and effectiveness of school-organised out-of-school activities. This large-scale survey with data from a total of 4,861 respondents therefore focuses on identifying the parameters of out-ofschool learning programmes run by primary schools. These parameters include the specific out-of-school learning places they attend, the frequency of and motivation for attendance and the methods of instruction used during these activities. I also wanted to find out about teacher and student attitudes towards out-of-school learning and whether there were any obstacles to these programmes that schools had to overcome and, if so, what these obstacles were as well as how much difficulty they presented. Two versions of an online questionnaire (one for headmasters and teachers and another for students) were sent to participating schools via the eDia (Electronic Diagnostic Assessment) platform. The results from the online survey indicate that primary schools follow the Hungarian National Core Curriculum recommendations on outof-school learning programmes, but such programmes only take place sporadically. Indeed, out-of-school learning cannot be considered a regular form of learning in Hungary even though the great majority of both teachers and students would be happy to participate in such activities with increased frequency. The teachers’ and headmasters’ responses suggest that the main reasons for the low prevalence of these programmes are difficulties with financial arrangements and the problem of fitting the programmes into the syllabus and weekly class schedule.